1998
DOI: 10.1084/jem.188.12.2369
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Switch Transcripts Is Required for Targeting of Antibody Class Switch Recombination

Abstract: Antibody class switching is mediated by somatic recombination between switch regions of the immunoglobulin heavy chain gene locus. Targeting of recombination to particular switch regions is strictly regulated by cytokines through the induction of switch transcripts starting 5′ of the repetitive switch regions. However, switch transcription as such is not sufficient to target switch recombination. This has been shown in mutant mice, in which the I-exon and its promoter upstream of the switch region were replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(95 citation statements)
references
References 33 publications
3
92
0
Order By: Relevance
“…It acts downstream of switch transcript-induced targeting of switch regions (26,27) and activation-induced cytidine deaminase (AID)-induced DNA breaks in the targeted switch regions (28). Id., identification.…”
Section: Discussionmentioning
confidence: 99%
“…It acts downstream of switch transcript-induced targeting of switch regions (26,27) and activation-induced cytidine deaminase (AID)-induced DNA breaks in the targeted switch regions (28). Id., identification.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that the germline switch transcripts, generated from an exon 5' of the switch region (I H ) and the C H exons (Lutzker et al 1988;Stavnezer-Nordgren & Sirlin 1986) are themselves required (Hein et al 1998). Switch transcripts are able to form stable RNA:DNA triplex structures with the switch region in vitro (Reaban & Gri¤n 1990).…”
Section: Hypermutation Class Switching and Transcriptionmentioning
confidence: 99%
“…During CSR, activation of B cells by cytokines activates the specific I promoter located 5 0 to the target C m or C x gene, and induces the synthesis and splicing of so-called germ line or sterile transcripts [Hein et al, 1998;Nagaoka et al, 2002]. This transcription step leads to the formation of RNA/ DNA hybrids on the template DNA strand, leaving the nontemplate DNA strand accessible to modification and cleavage [Chaudhuri et al, 2003;Yu et al, 2003;Ramiro et al, 2003;Dickerson et al, 2003].…”
Section: Transcription Of Targeted Dna Sequencesmentioning
confidence: 99%